Managing urbanisation and urban sprawl in Malaysia by using remote sensing and GIS applications - Rosni, Nur Aulia; Hj. Mohd. Noor, Norzailawati; Abdullah, Alias (Malaysian Institute of Planners, 2016)
In the global era, more than half of the world population live in urban area. With rapid urbanisation growth where the highest percentage concentrates in Asia, a relevant approach is needed to eliminate the possible threat that occurs after urbanisation took place; the urban sprawl. Urban sprawl is a popular term in academic discourse and has a long history but until these days, the concrete definition of this term is not yet configured. Many studies of sprawl have rooted back in non-Asian countries making the solution for sprawl is not suitable to be implemented in term of theories and practice. This research attempts to study the measurement of sprawl by using these geospatial indexes with Remote Sensing and GIS approach. The SPOT-5 images with 2.5 meters resolution were used to analyse the growth of sprawl in Kuala Lumpur metropolitan due to its high urbanisation rate. The findings show that Kuala Lumpur is a sprawling city. It is anticipated that this research will provide a new direction in urban sprawl studies and represent a robust analytic approach for characterizing urban development on the city scale at once as well as promoting a city via Remote Sensing and GIS technology.